Potential market entry of „Too Good To Go" in Prague - Dlabajova, Nikol; Král, Petr, 1979-; Henzl, Jindřich; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2020)
The main objective of this thesis is the analysis of the Czech market in regards to a potential market entry of the Danish company « Too Good To Go ». Using the economic PESTEL model, the author examines the Czech market using secondary data in its first theoretical part. Followed by the empirical part that includes quantitative research as well as a qualitative one. In the quantitative research the author elaborates on the demand for Too Good To Go’s service of consumers on the Czech market. In the qualitative research potential business partners are interviewed regarding their prior experience with similar businesses such as Too Good To Go and to investigate their interest for potential cooperation.
Vedoucí práce: Petr Král
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses